Effects of changes in temperature (local and central) on plasma fibrinolytic activity. Issue 4 (April 1973) - Dodman, B.; Cunliffe, W. J.; Roberts, B. E.; Buchan, C. W.
Abstract : The effect of local and whole-body heating and cooling on plasma fibrinolytic activity has been investigated in 59 subjects. An increase in whole-body temperature and both local cooling and heating increased the fibrinolytic activity. The results demonstrate that the application of local heat or cold will produce a local increase in fibrinolytic activity which is independent of general factors such as emotion and stress.